HUBUNGAN TINGKAT PENGETAHUAN DENGAN SIKAP REMAJA TENTANG SEKSUALITAS DI SMA NEGERI 5 KOTA BATAM TAHUN 2018 - Arianti, Desi; Sihombing, Sarmauli Franshisca (Universitas Batam, 2018)
Adolescence is a period when a child experiences puberty and starts looking for who they are, wants to go their own way and be treated specifically. This is where the symptoms of conformity appear, namely group pressure from peers. Using an analytical survey, the research design applied cross sectional which aims to observe the relationship between the independent variable and the dependent variable at the same time. It can be seen that the frequency of teenage knowledge is mostly good knowledge of 72 (79.1%) and less knowledgeable as many as 19 people (29.9). The results of further analysis obtained p-value = 0.004, in conclusion, there is a significant relationship between knowledge with the attitudes of adolescents about sexuality at SMA Negeri 5 Batam in 2018.